Critical density of Meloidogyne exigua in nursery coffee plants, Caturra variety - Rojas, Mainor (2013)
The purpose of this study was to evaluate the effect of increasing density of Meloidogyne exigua on the development of nursery plants. Coffee plantlets of the Caturra variety were transplanted into polyethylene bags with 1335 cm3 of disinfected substrate, to establish a trial with a randomized complete block design, with 8 replicates. The treatments applied included initial populations (Pi) of 0; 0,125; 0,25; 0,5; 1; 2; 4; 8; 16; 32 and 64 eggs + J2/cm3 substrate applied one month after transplant. The model y=m+(1-m) ZP-T applied 234 days after transplant to the height, diameter, number of nodes and aerial fresh weight, indicated that the tolerance limit (T) was 0,66; 0,06; 0,13 and 0,88 eggs + J2/cm3, respectively; the relative minimum production (m) was 0,79; 0,79; 0,33 and 0,54 respectively, at Pi equal to or higher than 64 eggs + J2/cm3. The gall index reached its maximum from a Pi of 2; the maximum peak of nematodes on the soil and roots was reached with a Pi between 2 and 4 while, the maximum rate of reproduction rate was 114 with a Pi of 0,125. It was concluded that the critical density was close to zero eggs/cm3 of substrate as initial population, and the nursery plants should develop free of nematodes since, even with a low Pi; it could reach the maximum population in a short time.